Search for the HH → bb[bar]bb[bar] process via vector-boson fusion production using proton-proton collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Jongmanns, Jan; Klassen, Martin; Kolb, Mathis; et al. (Journal of high energy physics, 2020)
A search for Higgs boson pair production via vector-boson fusion (VBF) in the bb̄bb̄ final state is carried out with the ATLAS experiment using 126 fb(-1) of proton-proton collision data delivered at √s = 13 TeV by the Large Hadron Collider. This search is sensitive to VBF production of additional heavy bosons that may decay into Higgs boson pairs, and in a non-resonant topology it can constrain the quartic coupling between the Higgs bosons and vector bosons. No significant excess relative to the Standard Model expectation is observed, and limits on the production cross-section are set at the 95% confidence level for a heavy scalar resonance in the context of an extended Higgs sector, and for non-resonant Higgs boson pair production. Interpretation in terms of the coupling between a Higgs boson pair and two vector bosons is also provided: coupling values normalised to the Standard Model expectation of kappa (2V) < -0.76 and kappa (2V) > 2.90 are excluded at the 95% confidence level in data.
ATLAS collaboration*: Christoph Anders, George Victor Andrei, Claire Antel, Arthur Bolz, Monica Dunford, Danilo Enoque Ferreira de Lima, Silvia Franchino, Louis Helary, Jan Jongmanns, Martin Klassen, Mathis Kolb, Anjali Krishnan, Andreas Kugel, Mykhailo Lisovyi, Hanno Meyer zu Theenhausen, Philipp Ott, Merve Sahinsoy, André Schöning, Hans-Christian Schultz-Coulon, Thomas Spieker, Rainer Stamen, Pavel Starovoitov, Stanislav Suchek, Luigi Vigani, Jike Wang, Sebastian Weber, Martin Wessels, Xiaoguang Yue [und 2898 weitere]
Im Titel steht der zweite und vierte Buchstabe b mit einem Oberstrich
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 12.02.2021